2017
DOI: 10.1107/s2053273316020350
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical investigation of orientation relationships and transformation strains in steels

Abstract: The identification of orientation relationships (ORs) plays a crucial role in the understanding of solid phase transformations. In steels, the most common models of ORs are the ones by Nishiyama-Wassermann (NW) and Kurdjumov-Sachs (KS). The defining feature of these and other OR models is the matching of directions and planes in the parent face-centred cubic γ phase to ones in the product body-centred cubic/tetragonal α/α' phase. In this article a novel method that identifies transformation strains with ORs is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…Discrete plots from the FCC and BCC phases shown in Fig. 2(e,f) respectively, reveal that {011} BCC // {111} FCC and <001> BCC // <011> FCC, indicating a Nishiyama-Wasserman orientation relationship between the lamellae 30 .…”
Section: (A)mentioning
confidence: 97%
“…Discrete plots from the FCC and BCC phases shown in Fig. 2(e,f) respectively, reveal that {011} BCC // {111} FCC and <001> BCC // <011> FCC, indicating a Nishiyama-Wasserman orientation relationship between the lamellae 30 .…”
Section: (A)mentioning
confidence: 97%
“…The base rotation matrix (OR 1 ) of each ideal relationship was calculated from the Euler angles defined for the transformation !, shown in Table 1. In order to obtain all the rotational matrices of each OR, we used the group of 24 rotations (P i ) that describes the symmetry of cubic crystals, summarized by Koumatos & Muehlemann (2017). Equation (1) was used to perform these calculations:…”
Section: Rotation Matrices Ideal Orientations and Misorientation Angmentioning
confidence: 99%
“…Simultaneous EBSD and EDS acquisition enables in-depth offline analysis of the region of interest, and we show results in Figure 2. We observe a strong orientation relationship in this field of view [18], which can be reconstructed using the Kudjimov -Sachs orientation relationship using the MTEX tool developed by Nyyssonen et al [19] (this reconstruction is not shown here). This can be observed not only within crystal orientation maps (shown colour coded with inverse pole figure colour with respect to the X and Z axes) as well as in the pole figure plots of the BCC and FCC phases.…”
Section: Bse Imaging In Reflection Modementioning
confidence: 58%